TRENDS AND DETERMINANTS OF FIRM VALUE - Cindy Olivia Angkasaputra (Universitas Mercu Buana Yogyakarta, 2021)
Due to the increase in the number of investors in Indonesia, businesses must work to raise their company's value in order to attract investors' attention. The value of the business should be a concern for both the business and the investors who utilize the value of the firm to make investment decisions. This research takes the form of a review of the literature on a number of recent studies on firm value undertaken in Indonesia. The research references are papers published between January 2019 and June 2021 in six journals accredited by SINTA (Science and Technology Index). The article discusses current trends in firm value research and the numerous determinants utilized. Numerous variables reflect the determinants of firm value, with firm size being the most often utilized independent variable. Numerous underlying theories explain the relationship between independent variables and firm value, with agency theory being the most often chosen by researchers. Several future research directions are discussed in this study in order to serve as references in the academic field and to inform enterprises about the variables that determine firm value.